(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
Cybersecurity is no longer just the concern of Information Technology (IT) teams. Emerging technologies like artificial intelligence and machine learning are changing the game for cybersecurity. To remain relevant and promote pedagogical framework, K-12 and institutions of higher education should continue to have conversations about cybersecurity education. As part of the paradigm shift cybersecurity education should be a priority. It is essential to equip administration, faculty, staff, and students with the dos and don’ts to ensure end users are not introducing a threat. Having a “cyber aware” student means they go home and to the 21st Century workforce exercising those same best practices. As the National Cybersecurity Alliance points out: this is Shared Responsibility. We each have to work together to keep ourselves, families, schools, communities and our nation safe. The object of this paper is to communicate on the subject of cybersecurity – across all sectors of government, business, academic institution and individual.